PESTLE Analysis of a Seaplane Transport Network in Greece - Dimitrios V. Siskos; Alexander Maravas; Ronald Mau (Aerospace)
Seaplane operations connect remote areas, promote tourism, and provide unique transportation solutions. After many years of preparations, commercial seaplane operations on a network of 100 water airports and 200 waterways in Greece are about to commence. The network can serve the needs of 1.6 million permanent residents of the Greek islands, the inhabitants of the mainland, and over 35 million annual tourists. This paper aims to conduct a PESTLE (Political, Economic, Social, Technological, Legal, and Environmental) analysis to identify the factors that have delayed operations and those that will affect the success of future operations. As such, 26 factors are examined. It was found that the Greek debt crisis and the COVID-19 pandemic were impediments to operations. The potential of using electric seaplanes is discussed. Recent developments in using drone inspection capabilities for aviation safety are examined. Management strategies for the Etesian winds and other environmental issues are presented. Overall, seaplane operations have enormous potential, while the Greek economic recovery provides favorable conditions for completing the project. The critical issue determining success is executing a multi-faceted business model to ensure seaplane operations’ financial viability. The network can act in synergy with other modes of transportation to help achieve social cohesion, improve tourism services, and foster economic development.